2010
DOI: 10.1021/ja100517v
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Cyclosporine: Access to N-Methylated Peptides via Isonitrile Coupling Reactions

Abstract: Recent developments in the use of isonitriles to furnish secondary and tertiary amide bond formations are applied to a novel total synthesis of the important cyclic polypeptide cyclosporine A. Specifically, the disclosed synthetic route demonstrates the utility of microwave-mediated carboxylic acid isonitrile couplings, thioacid isonitrile couplings at ambient temperature, and isonitrile-mediated couplings of carboxylic acids and thioacids with amines to form challenging amide bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
60
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 31 publications
1
60
0
8
Order By: Relevance
“…We continued our exploration in this method of amide formation using varying amines and thioacids (19,28,29). Coupling of solid-support glutamine 8 and leucine-derived thioacid 11 (19) under mediation by t-BuNC and HOBt, followed by cleavage from resin, provided dipeptide 12 in 94% yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We continued our exploration in this method of amide formation using varying amines and thioacids (19,28,29). Coupling of solid-support glutamine 8 and leucine-derived thioacid 11 (19) under mediation by t-BuNC and HOBt, followed by cleavage from resin, provided dipeptide 12 in 94% yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Coupling of solid-support glutamine 8 and leucine-derived thioacid 11 (19) under mediation by t-BuNC and HOBt, followed by cleavage from resin, provided dipeptide 12 in 94% yield (Fig. 2, Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Danishefsky et al have also demonstrated the reaction of thioacid and isonitrile as a possible way to access amides efficiently. 30,152 The chemistry was explored to synthesize Nmethylated peptides also (Scheme 68).…”
mentioning
confidence: 99%